Bahasa Mitik-Simbolik dari Antroposentris ke Kosmosentris - Agustinus Widyawan Purnomo Putra (Parahyangan Catholic University, 2020)
As homo religiosus, human being is always looking for the meaning of life, their existence, and also the mysteries of the universe. As time goes by, human being only focus for their self-fullness and self-centeredness and in the end human have lost con- nected with the ultimate reality in which they can get their bearing. Instead of searching for a meaning, man is becoming completely alienated from himself as a being, from the others, and from the transcendental things. In this era, it is important to have a new per- spective and world view about human being itself in the universe. That way is by way of mystic-symbolic language that not provide the objective truth but about how the truth is told or said. Therefore, with this experience or expression, humankind is invited to get involved and participate into which they has been born and never separated from.